2010
DOI: 10.1111/j.1365-4632.2010.04540.x
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic shaver with refinement for axillary osmidrosis

Abstract: Arthroscopic shaving for axillary osmidrosis has been associated with variable complication rates. Our experience has indicated that preservation of fibrovascular cords protected epidermis from necrosis and such refinement will allow for more optimal clinical result and lower complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In their report, there was no hematoma, flap necrosis or wound edge necrosis, except one local infection (1/60, 1.7%). 26 To eliminate the complications, we used modified suction-curettage shaving method instead of sparing of the 3-5 subcutaneous septa and got a result of no hematoma, no infection, and no skin necrosis with comparable improvements in bromhidrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In their report, there was no hematoma, flap necrosis or wound edge necrosis, except one local infection (1/60, 1.7%). 26 To eliminate the complications, we used modified suction-curettage shaving method instead of sparing of the 3-5 subcutaneous septa and got a result of no hematoma, no infection, and no skin necrosis with comparable improvements in bromhidrosis.…”
Section: Discussionmentioning
confidence: 99%
“…A few authors spared fibrous cords and perforating vessels during curettage by the SACS system. Chern et al [18] preserved fibrovascular bands and found a single adverse event involving 1 of 60 axillae. There were no recurrences.…”
Section: Sacs Systemmentioning
confidence: 99%
“…To our knowledge, only one comparative observation of the efficacy of curettage by the SACS system versus AO treatment by open excision has been published in Japanese [15] . The seven other English-language reports on AO treatment by closed-curettage SACS [2,14,[16][17][18][19][20] were uncontrolled clinical observations or case series, as listed in Table 2. During early SACS procedures, the tip of the outer cannula was open, which often accidentally perforated the axillary skin during the procedure [14,15] .…”
Section: Sacs Systemmentioning
confidence: 99%
See 2 more Smart Citations